The Effect of Clamshell Ash Substitution to the Mechanical Properties of Concrete. (October 2019) - Karolina, Rahmi; Rezeki, Ade Sri; Syahrizal,; Handana, M.AP.
Abstract: Concrete is the main material for construction that is widely used throughout the world. The more widespread use of concrete and the increasing scale of development also shows more and more concrete needs in the future. The era development of this rapid globalization era has resulted in the increasing number of used goods/waste whose existence can be a problem for life, one of which is the presence of clamshell ash. For this reason, many things have been done in order to recycle to overcome the problem of the existence of this waste. One of them is that clamshell ash can be used as a substitute for cement in a concrete mixture. This research uses clamshell ash and lime with variations of 0%, 5%, 10%, 15%, and 20% from the use of cement. The substitution of clamshell ash and lime affects the strength of the concrete. There are an increase in slump value with the substitution of clamshell ash by 8, 9, 11, 13, 14 and lime substitution by 8, 8, 5, 10, 12, 13. There are a decrease in compressive strength on the substitution of clamshell ash by 89.18%, 74.09%, 67.87%, 64.92% of normal concrete and compressive strength on lime substitution by 69.84%, 58.53%, 57.05 %, 55.82% of normal concrete. There are a decrease in split tensile strength in the substitution of clamshell ash by 95.96%, 92.3%, 81.7%, 75.8% of normal concrete and split tensile strength on lime substitution by 87.93%, 81.33%, 65, 92%, 48.37% of normal concrete.